2011
DOI: 10.1002/uog.8882
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcome following prenatal diagnosis of an isolated anomaly of the corpus callosum

Abstract: Objectives To assess the ability of prenatal ultrasound and magnetic resonance imaging (MRI) to diagnose isolated anomalies of the corpus callosum (ACC) and to further document the long-term prognosis following diagnosis. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 33 publications
6
57
1
1
Order By: Relevance
“…According to many authors - particularly in the articles written during the past decade - CCA is considered isolated when prenatal workup including MRI and genetic tests does not reveal any additional anomaly [5,9,10,11]. In fact, a positive family history (mental retardation, epilepsy and/or psychiatric disorders), parental consanguinity or certain abnormal findings observed during the pregnancy (such as nuchal anomaly, intrauterine growth retardation, infection, drug or alcohol addiction or reduced fetal movements) have to be carefully searched for.…”
Section: Corpus Callosum Dysgenesismentioning
confidence: 99%
“…According to many authors - particularly in the articles written during the past decade - CCA is considered isolated when prenatal workup including MRI and genetic tests does not reveal any additional anomaly [5,9,10,11]. In fact, a positive family history (mental retardation, epilepsy and/or psychiatric disorders), parental consanguinity or certain abnormal findings observed during the pregnancy (such as nuchal anomaly, intrauterine growth retardation, infection, drug or alcohol addiction or reduced fetal movements) have to be carefully searched for.…”
Section: Corpus Callosum Dysgenesismentioning
confidence: 99%
“…The prevalence in general population ranges from 1.8 to 7 per 10,000 births and may be seen in up to 2 %-3 % neuropediatric patients [6]. It may be sporadic or a genetic mutation may be present.…”
Section: Discussionmentioning
confidence: 98%
“…Prediction of the long-term pregnancy outcome and neurodevelopment in childhood depends on the type of defect and presence of the associated anomalies. In about 50% of the cases, ACC is an isolated finding and in the other half, the associated anomalies (both, cerebral and extra-cerebral) are found [23]. Due to the low frequency of prenatally diagnosed ACC in the general population and low rate of prenatal detection, the results, methodology and follow-up periods in studies on pregnancy outcome and neurodevelopment are heterogenic.…”
Section: Agenesis Of Corpus Callosum (Acc)mentioning
confidence: 99%
“…Due to the low frequency of prenatally diagnosed ACC in the general population and low rate of prenatal detection, the results, methodology and follow-up periods in studies on pregnancy outcome and neurodevelopment are heterogenic. Mangione et al, in their meta-analysis, revealed normal development in 71% of the newborns with isolated ACC [23]. On the other hand, the prognosis for fetuses with ACC and other anomalies remains poor.…”
Section: Agenesis Of Corpus Callosum (Acc)mentioning
confidence: 99%